QIBLA DIRECTION OF SHEIKH ARSYAD AL-BANJARI IN THE MAS'ĀLATUL QIBLA FĪ BATAWI’S BOOK - Adi Nugroho (Al-Hilal: Journal of Islamic Astronomy, 2023)
Facing the Qiblah as one of the legal requirements in carrying out the prayer requires us to determine where the Ka'bar building is located. Such things are not an obstacle for those who live around Mecca. In Indonesia, which is far from the physical building of the Ka’bah, the Qibla direction has often been a problem in society from time to time. Syekh Arsyad al-Banjari in his book Mas'ālatul Qibla fī Batawi provides a simple concept of how to face the Qibla for people who are far from the Kaaba, he also plays a role in straightening the Qibla direction of mosques in Betawi. This research uses a type of library research (Library Research). The data analysis process in this study uses descriptive analysis. Based on the research conducted by the author on the book, according to Sheikh Arsyad al-Banjari the obligation to face the Qibla with the ainul kaaba only applies to people who are in Mecca, so that areas outside Mecca may use a strong zhan. Furthermore, he was also of the opinion that it was advisable to change the Qibla direction of the mosque which was established by the wali if proven wrong. He practiced this by changing several mosques in Indonesia.